A rare presentation of systemic lupus erythematosus with lupus hepatitis - P., Sushrutha K.; Basavanagowda, Thanuja; R., Savitha M.; S., Prashanth; Ramu, A. (International Journal of Contemporary Pediatrics, 2021)
Systemic lupus erythematosus (SLE) is a chronic autoimmune disease characterized by multisystem inflammation and the presence of circulating autoantibodies directed against self-antigens. Prevalence of SLE in children and adolescents is 1-6 per 100,000 population. Liver dysfunction occurs in approximately in 50-60% of the patients with SLE.And the incidence of lupus hepatitis in diagnosed SLE patients is 9.3%. We are reporting a case of 11-year-old female child who presented with fever, skin rashes, oral ulcers, irritability and positive antinuclear antibody (ANA) with deranged liver function test (LFT) in the form of elevated transaminases, bilirubin level and altered coagulation profile. Hepatitis serology was negative, with low C3 levels, diagnosed as SLE with lupus hepatitis with lupus nephritis stage IV with psychosis. Clinical improvement along with improvement in terms of laboratory findings was seen on corticosteroids therapy. It is important to differentiate lupus hepatitis from autoimmune hepatitis (AIH) as AIH presents similar to lupus hepatitis, has poor prognosis. While lupus hepatitis being rare cause for mortality in patients with SLE has good response with early intervention with corticosteroids therapy.